Barriers and facilitators to knowledge translation activities within academic institutions in low- And middle-income countries - Kalbarczyk, Anna; Rodriguez, Daniela C; Mahendradhata, Yodi; Sarker, Malabika; Seme, Assefa; Majumdar, Piyusha; Akinyemi, Oluwaseun O; Kayembe, Patrick; Alonge, Olakunle O (Oxford Academic, 2022)
This article was published in the Health Policy and Planning by Oxford Academic [VC The Author(s) 2021. Published by Oxford University Press in association with The London School of Hygiene and Tropical Medicine.] and the definite version is available at: https://doi.org/10.1093/heapol/czaa188 The Journal's website is at: https://academic.oup.com/heapol/article/36/5/728/6154488